2010
DOI: 10.1002/adfm.201000539
|View full text |Cite
|
Sign up to set email alerts
|

Towards Efficient Dispersion of Carbon Nanotubes in Thermotropic Liquid Crystals

Abstract: Motivated by numerous recent reports indicating attractive properties of composite materials of carbon nanotubes (CNTs) and liquid crystals (LCs) and a lack of research aimed at optimizing such composites, the process of dispersing CNTs in thermotropic LCs is systematically studied. LC hosts can perform comparably or even better than the best known organic solvents for CNTs such as N‐methyl pyrrolidone (NMP), provided that the dispersion process and choice of LC material are optimized. The chemical structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 43 publications
0
57
0
Order By: Relevance
“…In light of the latter, CNTs are suitable candidates for emerging nanotechnological applications [16][17][18][19][20][21] . In fact, numerous ways of dispersing CNTs in matrices such as surfactants 22 , polymers [23][24][25] , biopolymers [26][27][28] , supramolecular organic gels 29,30 and liquid crystals [31][32][33][34][35][36] were meant to order structures. The use of any of the aforementioned matrices has resulted in hybrid materials, in which both morphology and order are mainly controlled by the matrix components, while CNTs lack any significant role.…”
mentioning
confidence: 99%
“…In light of the latter, CNTs are suitable candidates for emerging nanotechnological applications [16][17][18][19][20][21] . In fact, numerous ways of dispersing CNTs in matrices such as surfactants 22 , polymers [23][24][25] , biopolymers [26][27][28] , supramolecular organic gels 29,30 and liquid crystals [31][32][33][34][35][36] were meant to order structures. The use of any of the aforementioned matrices has resulted in hybrid materials, in which both morphology and order are mainly controlled by the matrix components, while CNTs lack any significant role.…”
mentioning
confidence: 99%
“…A sample chemical stability for resistance to acidic and high-temperature conditions [21][22][23][24]. The bottleneck that limits the use of CNTs as a gas-sensing material is their insufficient sensitivity to low concentrations of target gases.…”
Section: Preparation Of the Gas Sensormentioning
confidence: 99%
“…The effect of CNTs in the twisted nematic (TN)-LC device has been studied and found that the CNT doped cell reduces the switch-on voltage and improves the response time. 7 Effect of gold nano-particles (GNPs) on the memory of ferroelectric LC material has been reported and it was found that the memory is enhanced remarkably due to electric field induced charge transfer from LC molecules to the GNPs and the stabilization of helix deformation of deformed helix FLC material, which occurs on the application of electric field beyond a critical value. 9 The influence of gold nano-rods (GNRs) on the electro-optic and dielectric properties of the ferroelectric liquid crystals (FLCs) has also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The electro-optical characteristics of LC material, such as, Guest-host effect, bi-stability and field induced director axes re-orientation and switch-on voltage are important factors 1,2 for the display application. Recently, there has been enormous amount of research for the enhancement of electro-optical properties of LC materials by means of doping of metallic nano-particles (NPs), [3][4][5] carbon nano-tubes (CNTs) 6,7 and quantum dots 8 into the LC cell. The effect of CNTs in the twisted nematic (TN)-LC device has been studied and found that the CNT doped cell reduces the switch-on voltage and improves the response time.…”
Section: Introductionmentioning
confidence: 99%